Technical and Professional Writing: Solving Problems at Work - Kennedy, George; Montgomery, Tracy (Pearson, 2001)
Taking a research-based, integrated problem-solving approach to technical and professional writing, this text provides a model that illustrates real working-world solutions to problems that students are likely to encounter in the workplace. Each chapter begins with a short scenario case study that deals with theoretical or applied issues of technical and professional communication. The problem is carried through its development and resolution, thereby preparing students to deal appropriately and successfully in the professional world,